2021
DOI: 10.3892/or.2021.8179
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the interplay between pH receptors and immune cells: Potential drug targets (Review)

Abstract: Extracellular acidosis is associated with various immunopathological states. The microenvironment of numerous solid tumours and inflammatory responses during acute or chronic infection are all related to a pH range of 5.5-7.0. The relationship between inflammation and immune escape, cancer metabolism, and immunologic suppression drives researchers to focus on the effects of low pH on diverse components of disease immune monitoring. The potential effect of low extracellular pH on the immune function reveals the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…Thus, both types of nanosystems are suitable candidates to be used as nano drug delivery systems for oral administration. 67,68 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, both types of nanosystems are suitable candidates to be used as nano drug delivery systems for oral administration. 67,68 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, both types of nanosystems are suitable candidates to be used as nano drug delivery systems for oral administration. 67,68 Estimating the MIC of nanoantibiotic systems against E. coli Table 3 showed that all tested E. coli strains resisted to conventional doxycycline and Phyllanthus@NPs at all tested concentrations. However, the integration of AgNPs improved the antibacterial activity of Phyllanthus@AgNPs.…”
Section: S2 †)mentioning
confidence: 99%
“…TME and TD-EVs are known to work in harmony to disrupt NK cell function, thus, reducing the effectiveness of NK cell therapy. The acidic pH, as well as the immunosuppressive myeloid derived suppressor cells’ (MDSCs) and M2 macrophages’ presence in the TME, suppress the activation of NK cells, thereby compromising their cytotoxicity against a range of tumor cells [ 85 ]. Similarly, the TD-EVs were found to impair the function of NK cells through the transfer of multiple immunosuppressive factors (e.g., miRNAs and TGF-β) [ 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proliferation and function of most immune cells is not only dependent on the pH but also cell surface receptors, such as chemokine receptors, and oxygen levels [ 27 ]. In a solid tumor, combining the tumor hypoxia and the decrease in local pH, many published studies suggest there are devastating effects from lactic acid and hypoxia on various immune cell populations [ 15 , 30 , 31 ].…”
Section: Cancer Angiogenesis and The Tmementioning
confidence: 99%
“…Starting with monocytes, extracellular acidosis suppresses the expression of monocyte chemoattractant protein-1 (MCP1) and IL-6, both of which are critical for the maintenance of the pro-inflammatory M1 macrophage phenotype in the TME while at the same time promoting M1 to tumor-associated macrophage (TAM/M2) subtype transformation by increasing mannose receptor C-type 1 and arginase 1 expression [ 31 , 32 ]. The acidic environment also stimulates macrophages to produce IL-1β, which usually predicts a poor prognosis in many cancer types [ 32 , 33 ].…”
Section: Cancer Angiogenesis and The Tmementioning
confidence: 99%